Collagen supplementation and regenerative health: advances in biomarker detection and smart material integration - Ivaskiene, Tatjana; Viskelis, Jonas; Streimikyte, Paulina; Savickaitė, Milda; Mobasheri, Ali; Kaspute, Greta (Frontiers in Nutrition, 2025)
Collagen, the most abundant structural protein in the human body, plays a key role in skin integrity, tissue repair, and extracellular matrix organization. With increasing consumer and clinical interest, collagen supplementation has expanded rapidly, yet scientific evidence supporting its efficacy in anti-aging and regenerative applications remains inconsistent. This review critically evaluates current evidence on oral collagen supplementation, integrating insights from over 60 clinical studies assessing its effects on skin aging, musculoskeletal health, and hair disorders. Emerging data suggest that hydrolyzed collagen peptides may improve skin elasticity, joint function, and recovery after exercise, particularly when co-supplemented with vitamin C, silica, or resveratrol. Beyond supplementation, recent advances in biosensing and material science have enabled novel approaches to collagen detection and targeted delivery. Electrochemical, optical, and molecularly imprinted polymer (MIP)-based biosensors facilitate real-time monitoring of collagen biomarkers such as CTX-I, MMPs, and hydroxyproline, supporting precision assessment of collagen metabolism. In parallel, collagen-based hydrogels, nanoparticles, and electroresponsive scaffolds have shown promise as biocompatible carriers for controlled drug release and regenerative therapy. Collectively, these developments outline a translational framework connecting collagen supplementation, detection, and delivery. Continued integration of biosensing and smart material technologies may enhance clinical monitoring and therapeutic efficacy, advancing collagen-based interventions toward precision dermatology and regenerative medicine.